(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the effectiveness of Nutricare Gold powdered nutritional supplement in individuals needing recovery and health enhancement in Ninh Binh in 2024. Methods: A randomized controlled intervention study was conducted. Participants were people aged 50 to 70 years selected based on research criteria. The study was implemented and completed in Ninh Binh province in August 2024. The sample size included 120 individuals, with 60 in the intervention group receiving Nutricare Gold powder (50g per serving, twice daily for two months) and 60 in the control group following a regular diet. Results: After two months of intervention, the intervention group showed a decrease in total cholesterol by 0.96 mmol/L, LDL-c by 0.43 mmol/L, and triglycerides by 0.36 mmol/L, while total protein increased by 4.3 g/L and albumin by 3.6 g/L compared to the control group (p<0.05). The intervention group also reported a 51.7% reduction in poor appetite, 21.7% in digestive disorders/undigested stools, 11.6% in constipation, 28.4% in diarrhoea, and 28.4% in respiratory infections. Additionally, there was a 46.7% improvement in fatigue and lethargy, 33.4% in dizziness, 28.4% in weakness and skin dullness, and 51.7% in itching. Body weight increased by 3.7 kg, and the malnutrition rate decreased by 21.7%. Overall, 98.3% of participants reported being satisfied with the product. Conclusion: Supplementation with Nutricare Gold powder for people needing recovery and health improvement over two months effectively improved blood lipids, protein levels, and digestive health, enhancing overall nutrition and well-being.